2018
DOI: 10.1051/rees/2018004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hydropower resources in Tanzania. A review article

Abstract: The hydropower resources have become an attractive means of generating electricity to the off-grid network, especially in rural areas. This article assesses the small, mini and large hydropower resources and identified to reach 5.3 GW for electricity generation in Tanzania. The technology development discussed comprises of hydro turbine manufacturers, classification and turbine selection. The barriers presented include the presence of sediment in the hydropower reservoirs, financial viability, policy and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…This means that the approach should not be classic. In the absence of specific studies in all countries for rural areas like the one made by Mdee et al [16] for larger plants, it is important to promote capacity building and train the main people involved on how to develop micro renewable energy plants using a hands-on method. Still, we should study the social context in order to make sure the programme matches with the environment.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the approach should not be classic. In the absence of specific studies in all countries for rural areas like the one made by Mdee et al [16] for larger plants, it is important to promote capacity building and train the main people involved on how to develop micro renewable energy plants using a hands-on method. Still, we should study the social context in order to make sure the programme matches with the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Increased agricultural productivity, particularly through increased irrigation, and sustainable water resource management is viewed as fundamental to success, where hydrologic classifications provide information on the types and proportional representation of river systems of particular hydrological character that are likely to be affected by human development. In addition to irrigation water demand potentially set to increase by 7 billion cubic metres per year, several new dams and run‐of‐river hydropower plants are planned to produce 2.4 gigawatts of new hydroelectricity annually (Mdee et al, 2018; CDM Smith, 2016). This includes the planned construction of dams on the Ruhudji, Mnyera and Mpanga Rivers that will threaten Stable Perennial (StaPer) and Predictable Mid‐order Perennial hydrologic types, and dam construction on the Upper Kihansi River that will impact Stable Perennial (StaPer) and Variable Perennial (VarPer) hydrologic types in the Rufiji River Basin.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the planned construction of dams on the Ruhudji, Mnyera and Mpanga Rivers that will threaten Stable Perennial (StaPer) and Predictable Mid‐order Perennial hydrologic types, and dam construction on the Upper Kihansi River that will impact Stable Perennial (StaPer) and Variable Perennial (VarPer) hydrologic types in the Rufiji River Basin. Similarly, concentrated hydropower potential in western Tanzania (Mdee et al, 2018) would threaten a number of hydrologic classes, including the Low‐ (LWtSe) and Moderate‐elevation Wet Seasonal (MWtSe) classes and Montane (Monta) class. The controversial decision to begin construction of the Julius Nyerere Hydropower Project (JNHP) at Stiegler's gorge in July 2019, which will represent the fourth largest in Africa and ninth largest in the world, will similarly impact several of Tanzania's most valued rivers (Hamerlynck et al, 2011; Hoag & Öhman, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, Julius Nyerere hydro-electric power project is expected to add 2.1 GW of power (Aly et al, 2019). Mdee et al (2018) noted that Tanzania's small, mini and large hydropower resources are identified to reach 5.3 GW for electricity generation. However, there are barriers to hydropower development in Tanzania and this includes sediment in hydropower reservoirs and policy.…”
Section: Energy Supplymentioning
confidence: 99%